Influence of bio-ecological factors on population dynamics of a native biocontrol agent Aspergillus versicolor in arid soil - and SATISH LODHA*, VIJETA SINGH, RITU MAWAR (Indian Phytopathology, 2014)
The effects of microbial population, soil moisture and temperature on population dynamics of Aspergillus versicolor, a heat tolerant bio agent, were studied at different soil depths for a period of 12-months. The population of A. versicolor was highest at 6-10 cm but declined at 0-5 followed by 11-20 cm soil depths. At upper soil depths, decline in population of A. versicolor was estimated from July to September, but then a sudden upsurge was recorded. At 11–20 cm depth, progressive increase in population of A. versicolor was estimated from July to November, but it did not reach to the level recorded at other depths in the month of October. Population of A. versicolor, after 12 months was 48 and 80% higher at 6-10 and 11-20cm soil depth than the initial one but remained stationary at 0-5 cm. The total fungi mimics A. versicolor at all soil depths with positive correlation (P= 0.001), while its negative correlations were established with actinomycetes and soil moisture. Multiple regression equations accounted for almost 79-97% of variations in the population of A. versicolor by studied factors. Low residual factors in the path coefficient analysis also indicated that no other factor had significant contribution in influencing A. versicolor population. Studies revealed that minimum soil temperature and total bacteria played negligible role in influencing population of A. versicolor.